Highly efficient solution-processed blue-green organic light-emitting device

By using solution processing techniques with materials such as SimCP2 and BCP-BP-DMAC, a high-efficiency blue-green OLED without ACQ interference was prepared, solving the problem of low efficiency and short lifespan of blue OLEDs and achieving high-efficiency and wide-spectrum blue-green light emission.

CN116490019BActive Publication Date: 2026-11-06GUANGZHOU UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310319835.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-28
Publication Date
2026-11-06
Estimated Expiration
2043-03-28

AI Technical Summary

Technical Problem

Existing blue OLED devices suffer from low efficiency and short lifespan, especially due to the concentration aggregation quenching (ACQ) effect, which reduces external quantum efficiency.

Method used

Using three unique materials—the main body SimCP2 and the dyes BCP-BP-DMAC, BCP-BP-SFAC, and DCPC-BP-DMAC—and combined with solution processing technology, a high-efficiency blue-green organic light-emitting device is fabricated. By utilizing aggregation-induced delayed fluorescence (AIE) and thermally activated delayed fluorescence (TADF) properties, concentration aggregation quenching is avoided.

Benefits of technology

A highly efficient solution-processed blue-green organic light-emitting device with no concentration-induced quenching effect was achieved. The material is unaffected by ACQ and has high efficiency and a wide spectrum. The emission peak position gradually shifts from blue light to blue-green light, and the external quantum efficiency is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116490019B_ABST
    Figure CN116490019B_ABST
Patent Text Reader

Abstract

The application belongs to the field of organic light emitting devices, and discloses a high-efficiency solution processing type blue-green light organic light emitting device and a preparation method thereof, wherein the organic light emitting device is prepared by a structure composed of a host and a dye, the host is SimCP2 (bis [3,5-di (9H-carbazole-9-yl) phenyl] diphenylsilane), and the dye is any one of BCP-BP-DMAC, BCP-BP-SFAC and DCPC-BP-DMAC. By adopting the AIDF material, a suitable organic light emitting device structure is successfully set from the perspective of device preparation, and a high-efficiency solution processing type blue-green light organic light emitting device without concentration aggregation induced quenching effect is prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of organic light-emitting devices, and more specifically to a high-efficiency solution-processed blue-green organic light-emitting device. Background Technology

[0002] Organic light-emitting devices (OLEDs) have received widespread attention since they were first discovered and reported by Ching W. Tang in 1979 (Appl Phys Lett, 1987, 51: 913–915). After years of development, they have become a star product in the field of display lighting. In recent years, due to their advantages such as light weight, low cost, good flexibility, high color quality, ultra-fast response speed, wide viewing angle, and high contrast, they have been gradually used in televisions, mobile phones and other devices.

[0003] Although OLEDs are now widely used in various fields, some problems remain unresolved. As one of the three primary colors of optics, blue light, compared to red and green light, still suffers from issues such as lower efficiency and shorter lifespan in its light-emitting devices.

[0004] After years of development, OLED devices have adopted a sandwich-like structure consisting of a cathode, electron injection layer, electron transport layer, light-emitting layer, hole transport layer, hole injection layer, and anode. The principle is that electrons are injected from the cathode, with the electron injection and electron transport layers assisting in their transport to the light-emitting layer; holes are injected from the anode, with the hole injection and hole transport layers assisting in their transport to the light-emitting layer. Finally, electrons and holes recombine in the light-emitting layer to emit light. Therefore, the light-emitting layer significantly influences the device's emission wavelength and efficiency.

[0005] Solution-processed blue OLEDs have long required heavily doped emissive layer structures, meaning a high concentration of blue dye is necessary. On one hand, this has the advantage of ensuring sufficient host-guest energy transfer with increasing dye doping concentration, leading to high efficiency. However, on the other hand, with increasing doping concentration, exciton quenching between dye molecules becomes an intrinsic problem limiting device performance. Furthermore, aggregation-induced quenching (ACQ) reduces the intrinsic quantum efficiency of the emissive film, resulting in a decrease in the external quantum efficiency (EQE) (Chem. Rev. 2015, 115, 21, 11718–11940). Moreover, ACQ at high current densities significantly reduces device luminous efficiency, exacerbating the efficiency roll-off problem. Therefore, developing new blue emissive materials that avoid the ACQ problem has become a fundamental task. Summary of the Invention

[0006] To address the problems existing in the prior art, this invention proposes a novel solution-processed aggregation-induced emission high-efficiency solution-processed blue-green light-emitting device and its preparation method. Three unique materials were selected, and their aggregation-induced delayed fluorescence properties were confirmed. A high-efficiency solution-processed device was successfully prepared, which can broaden the emission spectrum of organic light-emitting devices and solve the problem of concentration aggregation quenching that exists in traditional blue light materials under high doping.

[0007] The objective of this invention is achieved through the following technical solution:

[0008] In a first aspect, the present invention provides a high-efficiency solution-processed blue-green organic light-emitting device, which is prepared by a structure composed of a host and a dye, wherein the host is SimCP2 (bis[3,5-bis(9H-carbazole-9-yl)phenyl]diphenylsilane), and the dye is any one of BCP-BP-DMAC, BCP-BP-SFAC, and DCPC-BP-DMAC;

[0009] The structural formula of the dye BCP-BP-DMAC is as follows:

[0010]

[0011] (4-(9,9-dimethylacridin-10(9H)-yl)phenyl)(9,9'-diphenyl-9H,9'H-[3,3'-bicarbazol]-6-yl)methanone;

[0012] The structural formula of the dye BCP-BP-SFAC is as follows:

[0013]

[0014] (4-(10H-spiro[acridine-9,9'-fluoren]-10-yl)phenyl)(9,9'-diphenyl-9H,9'H-[3,3'-bicarbazol]-6-yl)methanone;

[0015] The structural formula of the dye DCPC-BP-DMAC is as follows:

[0016]

[0017] (9-(4-(1-(4-(9H-carbazol-9-yl)phenyl)cyclohexyl)phenyl)-9H-carbazol-3-yl)(4-(9,9-dimethylacridin-10(9H)-yl)phenyl)methanone.

[0018] More preferably, the dye is selected as BCP-BP-DMAC, namely (4-(9,9-dimethylacridin-10(9H)-yl)phenyl)(9,9'-diphenyl-9H,9'H-[3,3'-bicarbazol]-6-yl)methanone[(4-(9,9-dimethylacridin-10(9H)-yl)phenyl)(9,9'-diphenyl-9H,9'H-[3,3'-bicarbazol]-6-yl)methanone].

[0019] Among them, the main body can play the role of dispersing the object, assisting the energy transfer of the luminescent layer and regulating the spectrum; the aggregation-induced delayed fluorescence material serves as a dye and as the luminescent main body.

[0020] Secondly, the present invention provides a method for preparing a high-efficiency solution-processed blue-green organic light-emitting device, comprising the following steps:

[0021] (1) Solution preparation:

[0022] SimCP2 and BCP-BP-DMAC were dissolved in chlorobenzene and stirred thoroughly on a heating plate. Then, the SimCP2 solution and BCP-BP-DMAC solution were mixed according to the dye ratio to form a stock solution.

[0023] (2) Substrate pretreatment:

[0024] The indium tin oxide (ITO) substrate was thoroughly cleaned, then the surface liquid was dried with nitrogen and dried. The substrate was then placed in an ultraviolet ozone generator for ozone treatment.

[0025] (3) Preparation of the hole transport layer:

[0026] After ozone treatment, the film was spin-coated with PEDOT:PSS solution on a spin coater, then dried in an oven, and finally transferred to a glove box.

[0027] (4) Preparation of the light-emitting layer:

[0028] After filtering the stock solution through a 0.22 μm filter, it was spin-coated onto the PEDOT:PSS layer at a spin speed of 1800 r / min, and then placed on a heating stage for annealing.

[0029] (5) Fabrication of the electron transport layer:

[0030] Transfer the spin-coated device to a vacuum evaporation machine and deposit it onto the light-emitting layer in the order of first depositing DPEPO and then depositing TmPyPB.

[0031] (6) Preparation of the cathode:

[0032] Then, lithium fluoride was deposited first, followed by aluminum, onto the electron transport layer, and the device fabrication was completed.

[0033] Preferably, during the solution preparation process, SimCP2 and BCP-BP-DMAC are dissolved in chlorobenzene respectively, and the concentration of the solutions prepared is 10 mg / mL.

[0034] Preferably, during the solution preparation process, the solution is stirred thoroughly at 40°C on a heating platform for 4 hours.

[0035] Preferably, during the solution preparation process, the concentration ratio of SimCP2 to BCP-BP-DMAC is x%, where x = 1 to 100%.

[0036] Preferably, during the substrate pretreatment process, the drying temperature is 120°C and the ozone treatment time is 20 minutes.

[0037] Preferably, in the preparation of the hole transport layer, the spin coating speed is 4000 r / min, the oven temperature is 120℃, and the drying time is 30 min.

[0038] Preferably, in the preparation of the light-emitting layer, the spin coating speed is 1800 r / min, the annealing temperature is 100℃, and the annealing time is 30 min.

[0039] Preferably, in the preparation of the electron transport layer, DPEPO is deposited at 10 nm and TmPyPB is deposited at 50 nm.

[0040] Preferably, in the preparation of the cathode, lithium fluoride is deposited at 1 nm and aluminum is deposited at 100 nm.

[0041] The beneficial effects of this invention are as follows:

[0042] 1. The AIDF material used in this invention is a material with unique properties. Furthermore, from the perspective of device fabrication, this invention has successfully set up a structure suitable for organic light-emitting devices and fabricated a solution-processed blue-green organic light-emitting device with no concentration aggregation-induced quenching effect and high efficiency.

[0043] 2. The advantage of this invention is that the materials of the prepared organic light-emitting device are not affected by ACQ, and while having the properties of AIE, they also have the high efficiency of TADF. Attached Figure Description

[0044] The present invention will be further described with reference to the accompanying drawings, but the embodiments in the drawings do not constitute any limitation on the present invention. For those skilled in the art, other drawings can be obtained based on the following drawings without creative effort.

[0045] Figure 1 This is a diagram illustrating the luminescence mechanism of the thermally activated delayed fluorescence material in the organic light-emitting device according to an embodiment of the present invention.

[0046] Figure 2 This invention relates to the BCP-BP-DMAC solution in a chlorobenzene solution at 10°C. -5 Photoluminescence spectrum of intrinsic state dilute solution at mol / L.

[0047] Figure 3 In this embodiment of the invention, tetrahydrofuran and water are used to prepare 10 different water contents. -5 Photoluminescence spectra of suspensions with water contents of 10%, 60%, and 90% in mol / L.

[0048] Figure 4 In this embodiment of the invention, tetrahydrofuran and water are used to prepare 10 different water contents. -5 Exciton fluorescence lifetime in mol / L suspension with 10% water content.

[0049] Figure 5 In this embodiment of the invention, tetrahydrofuran and water are used to prepare 10 different water contents. -5 Fluorescence lifetime of excitons in a mol / L suspension with 90% water content.

[0050] Figure 6 In this embodiment of the invention, tetrahydrofuran and water are used to prepare 10 different water contents. -5 Relative photoluminescence intensity at different water contents in mol / L suspensions (with 90% fluorescence intensity defined as 100% intensity).

[0051] Figure 7 In this embodiment of the invention, tetrahydrofuran and water are used to prepare 10 different water contents. -5 Fluorescence quantum efficiency at different water contents in mol / L suspensions.

[0052] Figure 8 This is an embodiment of the present invention, DMAC-DPS in chlorobenzene solution for 10... -5 Photoluminescence spectrum of intrinsic state dilute solution per mole per liter.

[0053] Figure 9 This is an exciton fluorescence lifetime diagram of DMAC-DPS in an embodiment of the present invention.

[0054] Figure 10The voltage and current curves are for the device with a light-emitting layer of 10% BCP-BP-DMAC:SimCP2 in Embodiment 1 of the present invention.

[0055] Figure 11 The voltage-electroluminescence brightness curve is shown for the device with a light-emitting layer of 10% BCP-BP-DMAC:SimCP2 in Example 1.

[0056] Figure 12 The current density external quantum efficiency curve is shown for the device with a light-emitting layer of 10% BCP-BP-DMAC:SimCP2 in Example 1.

[0057] Figure 13 The image shows the electroluminescence spectrum of the device with a 10% BCP-BP-DMAC:SimCP2 emitting layer in Example 1. The emission peak of the device is 479 nm.

[0058] Figure 14 The voltage-current curves are for the device with a 20% BCP-BP-DMAC:SimCP2 light-emitting layer as described in Example 2.

[0059] Figure 15 The voltage-electroluminescence brightness curve of the device with a light-emitting layer of 20% BCP-BP-DMAC:SimCP2 in Example 2 is shown. The maximum brightness of the device is 1342 candela per square centimeter.

[0060] Figure 16 The current density external quantum efficiency curve is shown for the device with a 20% BCP-BP-DMAC:SimCP2 light-emitting layer in Example 2. The maximum external quantum efficiency of the device is 8.8%.

[0061] Figure 17 The image shows the electroluminescence spectrum of the device with a 20% BCP-BP-DMAC:SimCP2 emitting layer in Example 2. The emission peak of the device is 480 nm.

[0062] Figure 18 The voltage-current curves are for the device in Example 3 with a light-emitting layer of 30% BCP-BP-DMAC:SimCP2.

[0063] Figure 19 This is the voltage-electroluminescence brightness curve of the device with a 30% BCP-BP-DMAC:SimCP2 light-emitting layer in Example 3. The maximum brightness of the device is 1592 candela per square centimeter.

[0064] Figure 20 The current density external quantum efficiency curve is shown for the device with a 30% BCP-BP-DMAC:SimCP2 light-emitting layer in Example 3. The maximum external quantum efficiency of the device is 14.9%.

[0065] Figure 21 The image shows the electroluminescence spectrum of the device with a 30% BCP-BP-DMAC:SimCP2 emitting layer in Example 3. The emission peak of the device is 484 nm.

[0066] Figure 22 The voltage-current curves are for the device in Example 4 with a light-emitting layer of 50% BCP-BP-DMAC:SimCP2.

[0067] Figure 23 This is the voltage-electroluminescence brightness curve of the device with a 50% BCP-BP-DMAC:SimCP2 emitting layer in Example 4. The maximum brightness of the device is 1591 candela per square centimeter.

[0068] Figure 24 This is the current density external quantum efficiency curve for the device in Example 4, where the emitting layer is 50% BCP-BP-DMAC:SimCP2. The maximum external quantum efficiency of the device is 12.2%.

[0069] Figure 25 This is the electroluminescence spectrum of the device in Example 4, where the emitting layer is 50% BCP-BP-DMAC:SimCP2. The emission peak of the device is at 489 nm.

[0070] Figure 26 The voltage-current curves are for the device in Example 5 with a light-emitting layer of 70% BCP-BP-DMAC:SimCP2.

[0071] Figure 27 This is the voltage-electroluminescence brightness curve of the device with a 70% BCP-BP-DMAC:SimCP2 light-emitting layer in Example 5. The maximum brightness of the device is 1836 candela per square centimeter.

[0072] Figure 28 This is the current density external quantum efficiency curve for the device in Example 5, where the emitting layer is 70% BCP-BP-DMAC:SimCP2. The maximum external quantum efficiency of the device is 8.7%.

[0073] Figure 29 This is the electroluminescence spectrum of the device in Example 5, whose emitting layer is 70% BCP-BP-DMAC:SimCP2. The emission peak of the device is at 495 nm.

[0074] Figure 30 The voltage and current curves are for the device with a 10% DMAC-DPS:SimCP2 light-emitting layer as Comparative Example 1.

[0075] Figure 31 The above is the voltage-electroluminescence brightness curve of the device with a 10% DMAC-DPS:SimCP2 emitting layer (Comparative Example 1). The maximum brightness of the device is 573 candela per square centimeter.

[0076] Figure 32 The current density external quantum efficiency curves are shown for the device with a 10% DMAC-DPS:SimCP2 emitting layer (Comparative Example 1). The maximum external quantum efficiency of the device is 4.1%.

[0077] Figure 33 The image shows the electroluminescence spectrum of the device with a 10% DMAC-DPS:SimCP2 emitting layer (Comparative Example 1). The emission peak of the device is at 465 nm.

[0078] Figure 34 The voltage and current curves are for the device with a 20% DMAC-DPS:SimCP2 light-emitting layer (Comparative Example 2).

[0079] Figure 35 The above is the voltage-electroluminescence brightness curve of the device with a 20% DMAC-DPS:SimCP2 emitting layer (Comparative Example 2). The maximum brightness of the device is 722 candela per square centimeter.

[0080] Figure 36 The current density external quantum efficiency curves are shown for the device with a 20% DMAC-DPS:SimCP2 emitting layer (Comparative Example 2). The maximum external quantum efficiency of the device is 3.8%.

[0081] Figure 37 The image shows the electroluminescence spectrum of the device with a 20% DMAC-DPS:SimCP2 emitting layer (Comparative Example 2). The emission peak of the device is at 466 nm.

[0082] Figure 38 The voltage and current curves are for the device with a 30% DMAC-DPS:SimCP2 light-emitting layer as Comparative Example 3.

[0083] Figure 39 The above is the voltage-electroluminescence brightness curve of the device with a 30% DMAC-DPS:SimCP2 emitting layer (Comparative Example 3). The maximum brightness of the device is 812 candela per square centimeter.

[0084] Figure 40 The current density external quantum efficiency curves are shown for the device in Comparative Example 3, which has a 30% DMAC-DPS:SimCP2 emitting layer. The maximum external quantum efficiency of the device is 3.6%.

[0085] Figure 41 The image shows the electroluminescence spectrum of the device in Comparative Example 3, whose emitting layer is 30% DMAC-DPS:SimCP2. The emission peak of the device is at 469 nm. Detailed Implementation

[0086] To more clearly illustrate the present invention and to gain a clearer understanding of its technical features, objectives, and beneficial effects, the technical solution of the present invention will now be described in detail below, but this should not be construed as limiting the scope of the present invention.

[0087] (1) Explanation of relevant proper nouns:

[0088] TADF: Thermally Activated Delayed Fluorescence.

[0089] ACQ: Aggregation-Caused Quenching.

[0090] AIE: Aggregation-Induced Emission.

[0091] PEDOT:PSS solution is an aqueous solution of a high molecular weight polymer.

[0092] (2) Explanation of the contents related to this invention:

[0093] Organic light-emitting materials, after years of research, are generally classified into fluorescent materials, phosphorescent materials, and thermally activated delayed fluorescence (TADF) materials. Among them, traditional fluorescent materials, due to their properties, cannot effectively utilize excitons, with a theoretical maximum exciton utilization rate of only 25%. Phosphorescent materials and TADF materials also have 100% exciton utilization rates. However, since phosphorescent materials mostly contain heavy metals, the lower-cost and environmentally friendly TADF materials have become the main choice today.

[0094] Thermally activated delayed fluorescence materials are characterized by a small energy level difference between their singlet and triplet states. This allows them to absorb heat from the environment, enabling excitons in the triplet state to undergo reverse intersystem crossing (RISC) to emit light in the singlet state, thus achieving full utilization of the excitons. The principle is as follows: Figure 1 As shown.

[0095] Most existing organic light-emitting blue light-emitting devices use highly efficient TADF materials as the light-emitting host. However, due to the ACQ effect of the material, the device fabrication process often involves doping the host with the light-emitting dye. On the one hand, as the dye concentration increases, the energy transfer between the host and guest becomes more efficient; on the other hand, as the dye concentration increases, excitons accumulate in the dye, and the ACQ effect becomes more pronounced, leading to an increase in exciton nonradiative recombination and a decrease in external quantum efficiency.

[0096] AIDF materials, which combine the properties of AIE (higher aggregation degree, higher luminescence) and TADF (high exciton utilization), were invented under these circumstances. They attracted attention immediately upon publication and experienced rapid development. However, most AIDF materials themselves have poor solubility, and solution-processed AIDF blue light devices have not developed as well as vapor-deposited AIDF blue light devices.

[0097] However, the high vacuum environment inherent in vapor-deposited devices leads to expensive fabrication equipment and high energy consumption. Panel size is also limited by equipment volume, hindering continuous production. These are all current concerns. Solution-processed devices, theoretically offering advantages such as 100% material utilization, low cost, continuous production capability, and ease of fabrication for large-area devices, have attracted considerable attention. However, due to limitations in materials and fabrication processes, solution-processed light-emitting devices still lag behind vapor-deposited devices to some extent. Therefore, providing a feasible and efficient fabrication method for solution-processed devices is essential.

[0098] Unless otherwise specified, the raw materials, reagents or devices used in the following examples are available from conventional commercial sources or can be obtained by existing known methods.

[0099] The present invention will be further described in conjunction with the following embodiments.

[0100] Basic Implementation

[0101] See appendix Figure 1-41 The high-efficiency solution-processed blue-green organic light-emitting device provided in this embodiment of the invention is prepared by a structure composed of a host and a dye. The host is SimCP2 (bis[3,5-bis(9H-carbazole-9-yl)phenyl]diphenylsilane), and the dye is any one of BCP-BP-DMAC, BCP-BP-SFAC, and DCPC-BP-DMAC.

[0102] As a basic embodiment, when SimCP2 is selected as the main component, the dye selected is the thermally activated delayed fluorescence molecule BCP-BP-DMAC. The fabrication steps of this high-efficiency solution-processed blue-green organic light-emitting device include:

[0103] 1. Solution preparation:

[0104] SimCP2 and BCP-BP-DMAC were dissolved in chlorobenzene to prepare a solution of 10 mg / mL, and stirred thoroughly at 40°C for four hours. Then, the SimCP2 solution and the BCP-BP-DMAC solution were mixed to prepare a stock solution according to the dye concentration percentage x% (x = 1 to 100%).

[0105] 2. Substrate pretreatment:

[0106] The indium tin oxide (ITO) substrate was thoroughly cleaned with water, ethanol, and a cleaning solution. The surface liquid was then dried with nitrogen gas, followed by drying in an oven at 120°C. The substrate was then subjected to ozone treatment in a UV ozone generator for 20 minutes.

[0107] 3. Preparation of the hole transport layer

[0108] After ozone treatment, the film was spin-coated with PEDOT:PSS on a spin coater at a speed of 4000 rpm. Then it was placed in an oven at 120°C for 30 minutes and then transferred to a glove box.

[0109] 4. Preparation of the light-emitting layer

[0110] The stock solution was filtered through a 0.22 μm filter and then spin-coated onto a PEDOT:PSS layer at a spin speed of 1800 rpm. After that, it was placed on a heating plate and annealed at 100 °C for 30 minutes.

[0111] 5. Electron transport layer

[0112] The device with the spin-coated light-emitting layer is transferred to a vacuum evaporation machine and deposited onto the light-emitting layer in the order of 10 nm DPEPO and 50 nm TmPyPB.

[0113] 6. Cathode Preparation

[0114] Then, lithium fluoride is deposited at a density of 1 nanometer and aluminum at a density of 100 nanometers onto the electron transport layer in sequence, and the device fabrication is completed.

[0115] Example 1

[0116] The high-efficiency solution-processed blue-green organic light-emitting device and its fabrication method provided in this embodiment are the same as those in the basic embodiment, specifically:

[0117] A stock solution was prepared with a dye concentration of 10%, i.e., x = 10%.

[0118] Example 2

[0119] A method for fabricating a high-efficiency solution-processed blue-green organic light-emitting device is basically the same as the basic embodiment, except that:

[0120] A stock solution was prepared with a dye concentration of 20%, i.e., x = 20%.

[0121] Example 3

[0122] A method for fabricating a high-efficiency solution-processed blue-green organic light-emitting device is basically the same as the basic embodiment, except that:

[0123] A stock solution was prepared with a dye concentration of 30%, i.e., x = 30%.

[0124] Example 4

[0125] A method for fabricating a high-efficiency solution-processed blue-green organic light-emitting device is basically the same as the basic embodiment, except that:

[0126] A stock solution was prepared with a dye concentration of 50%, i.e., x = 50%.

[0127] Example 5

[0128] A method for fabricating a high-efficiency solution-processed blue-green organic light-emitting device is basically the same as the basic embodiment, except that:

[0129] The stock solution was prepared with a BCP-BP-DMAC ratio of 70%, i.e., x = 70%.

[0130] Comparison with basic implementation

[0131] The main component is SimCP2, and the dye chosen is the thermally activated delayed fluorescence molecule DMAC-DPS, specifically the thermally activated delayed fluorescence blue material 10,10'-(dimethylsulfonylbis(4,1-phenylene))bis(9,9-dimethyl-9,10-dihydroacridine)], abbreviated as DMAC-DPS, with the molecular formula:

[0132]

[0133] 1. Solution preparation:

[0134] SimCP2 and DMAC-DPS were dissolved in chlorobenzene to prepare a solution of 10 mg / mL, and stirred thoroughly at 40°C for four hours. Then, the SimCP2 solution and DMAC-DPS solution were mixed to prepare a stock solution according to the dye percentage x% (x = 1 to 100%).

[0135] 2. Substrate pretreatment:

[0136] The indium tin oxide (ITO) substrate was thoroughly cleaned with water, ethanol, and a cleaning solution. The surface liquid was then dried with nitrogen gas, followed by drying in an oven at 120°C. The substrate was then subjected to ozone treatment in a UV ozone generator for 20 minutes.

[0137] 3. Preparation of the hole transport layer

[0138] After ozone treatment, the film was spin-coated with PEDOT:PSS on a spin coater at a speed of 4000 rpm. Then it was placed in an oven at 120°C for 30 minutes and then transferred to a glove box.

[0139] 4. Preparation of the light-emitting layer

[0140] The stock solution was filtered through a 0.22 μm filter and then spin-coated onto a PEDOT:PSS layer at a spin speed of 1800 rpm. After that, it was placed on a heating plate and annealed at 100 °C for 30 minutes.

[0141] 5. Electron transport layer

[0142] The device with the spin-coated light-emitting layer is transferred to a vacuum evaporation machine and deposited onto the light-emitting layer in the order of 10 nm DPEPO and 50 nm TmPyPB.

[0143] 6. Cathode Preparation

[0144] Then, lithium fluoride is deposited at a density of 1 nanometer and aluminum at a density of 100 nanometers onto the electron transport layer in sequence, and the device fabrication is completed.

[0145] Comparative Example 1

[0146] A method for fabricating an organic light-emitting device is substantially the same as that in the comparative basic embodiment, except that:

[0147] The stock solution is prepared with a DMAC-DPS ratio of 10%, i.e., x = 10%.

[0148] Comparative Example 2

[0149] A method for fabricating an organic light-emitting device is substantially the same as that in the comparative basic embodiment, except that:

[0150] The stock solution was prepared with a DMAC-DPS ratio of 20%, i.e., x = 20%.

[0151] Comparative Example 3

[0152] A method for fabricating an organic light-emitting device is substantially the same as that in the comparative basic embodiment, except that:

[0153] The stock solution is prepared with a DMAC-DPS ratio of 30%, i.e., x = 30%.

[0154] Table 1 Comparison of data from comparative examples and embodiments

[0155]

[0156] As can be seen in the comparison, with ordinary thermally activated delayed fluorescence materials as the emitting layer, although the maximum brightness increases due to more complete host-guest energy transfer, the turn-on voltage also increases to some extent as the material proportion increases, and the external quantum efficiency decreases with increasing concentration, clearly affected by the concentration quenching effect. As can be seen in the embodiments, the material used in this patent, with an increased material proportion, also achieves more complete host-guest energy transfer, but its turn-on voltage gradually decreases. Furthermore, the highest external quantum efficiency is obtained at a high concentration (30%), and a not-low maximum external quantum efficiency is also achieved at ultra-high concentrations. The maximum emission wavelength of the device gradually redshifts from 479 nm to 495 nm, and the emission gradually changes from blue light to blue-green light.

[0157] Analysis of the relevant graphs:

[0158] Figure 2 It is BCP-BP-DMAC in chlorobenzene solution for 10 -5 Photoluminescence spectrum of intrinsic state dilute solution at molar per liter. The emission peak is at 535 nm. The intrinsic state dilute solution exhibits a greenish tint.

[0159] 10 different water contents were prepared using tetrahydrofuran and water. -5 Because tetrahydrofuran is immiscible with water and the solvent is insoluble in water, the material will aggregate in tetrahydrofuran. As the water content increases, the degree of aggregation increases. Figure 3 This is a photoluminescence spectrum of a portion of the water content.

[0160] Figure 4 This is a fluorescence lifetime diagram of excitons with 10% water content. Figure 5 This is an exciton fluorescence lifetime diagram with 90% water content. It can be seen that when the intermolecular distance is large, the molecules exhibit a short lifetime and no delayed fluorescence; however, in the aggregated state, the exciton fluorescence lifetime is greatly increased, exhibiting delayed fluorescence, demonstrating the properties of thermally activated delayed fluorescence.

[0161] Figure 6 The graph shows the relative photoluminescence intensity at different water contents (with 90% fluorescence intensity as 100% intensity). It can be seen that as the water content increases, there is a significant increase in photoluminescence intensity after 60% water content. Furthermore, the higher the water content, the more aggregated the molecules become, resulting in higher intensity. This indicates that the molecules are aggregation-induced emission molecules. Figure 7 The fluorescence quantum efficiency data in Table 1 also confirm this result. Furthermore, as the water content increases, the spectrum gradually blue-shifts, reaching a peak emission position of 517 nm at a water content of 90%, which is blue-green.

[0162] Table 1. Maximum emission wavelength and fluorescence quantum efficiency for different water contents.

[0163]

[0164] Figure 8 DMAC-DPS in chlorobenzene solution for 10 -5 The photoluminescence spectrum of the intrinsic state dilute solution with moles per liter has an emission peak at 492 nm, which is blue light, similar to that of the example.

[0165] Figure 9 The image shows the exciton fluorescence lifetime of DMAC-DPS, which exhibits delayed fluorescence, confirming that it is thermally activated delayed fluorescence.

[0166] The AIDF material used in the above embodiments of the present invention is a material with unique properties. Furthermore, from the perspective of device fabrication, the present invention has successfully set up a structure suitable for organic light-emitting devices and fabricated a solution-processed blue-green organic light-emitting device with no concentration aggregation-induced quenching effect and high efficiency.

[0167] The organic light-emitting devices prepared in the above embodiments of the present invention are free from ACQ influence, possess the properties of AIE, and also have the high efficiency of TADF.

[0168] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the essence and scope of the technical solutions of the present invention.

Claims

1. A high-efficiency solution-processed blue-green organic light-emitting device, characterized in that, It is prepared by a structure consisting of a host and a dye, wherein the host is SimCP2 (bis[3,5-di(9H-carbazole-9-yl)phenyl]diphenylsilane), and the dye is BCP-BP-DMAC, namely (4-(9,9-dimethylacridin-10(9-hydro)-yl)phenyl)(9,9'-diphenyl-9-hydro,9'-[3,3'-bicarbazole]-6-yl) methyl ketone; The structural formula of the dye BCP-BP-DMAC is as follows: ; The method for fabricating the high-efficiency solution-processed blue-green organic light-emitting device includes the following steps: (1) Solution preparation: SimCP2 and BCP-BP-DMAC were dissolved in chlorobenzene and stirred thoroughly on a heating plate. Then, the SimCP2 solution and BCP-BP-DMAC solution were mixed according to the dye ratio to form a stock solution. (2) Substrate pretreatment: The indium tin oxide (ITO) substrate was thoroughly cleaned, then the surface liquid was dried with nitrogen and dried. The substrate was then placed in an ultraviolet ozone generator for ozone treatment. (3) Preparation of the hole transport layer: After ozone treatment, the film was spin-coated with PEDOT:PSS solution on a spin coater, then dried in an oven, and finally transferred to a glove box. (4) Preparation of the light-emitting layer: After filtering the stock solution through a 0.22 μm filter, it was spin-coated onto the PEDOT:PSS layer at a spin speed of 1800 r / min, and then placed on a heating stage for annealing. (5) Fabrication of the electron transport layer: Transfer the spin-coated device to a vacuum evaporation machine and deposit it onto the light-emitting layer in the order of first depositing DPEPO and then depositing TmPyPB. (6) Preparation of the cathode: Then, lithium fluoride was deposited first, followed by aluminum, onto the electron transport layer, and the device fabrication was completed.

2. The high-efficiency solution-processed blue-green organic light-emitting device according to claim 1, characterized in that, In the solution preparation process, SimCP2 and BCP-BP-DMAC are dissolved in chlorobenzene respectively, and the concentration of the solutions prepared is 10 mg / mL; the concentration ratio of dyes in the stock solution is x%, x = 10-70%.

3. The high-efficiency solution-processed blue-green organic light-emitting device according to claim 1, characterized in that, During the solution preparation process, the solution is stirred thoroughly at 40°C on a heating platform for 4 hours.

4. The high-efficiency solution-processed blue-green organic light-emitting device according to claim 1, characterized in that, During the substrate pretreatment process, the drying temperature is 120°C and the ozone treatment time is 20 minutes.

5. The high-efficiency solution-processed blue-green organic light-emitting device according to claim 1, characterized in that, In the preparation of the hole transport layer, the spin coating speed is 4000 r / min, the oven temperature is 120℃, and the drying time is 30 min.

6. The high-efficiency solution-processed blue-green organic light-emitting device according to claim 1, characterized in that, In the preparation of the light-emitting layer, the spin coating speed is 1800 r / min, the annealing temperature is 100℃, and the annealing time is 30 min.

7. The high-efficiency solution-processed blue-green organic light-emitting device according to claim 1, characterized in that, In the preparation of the electron transport layer, DPEPO is deposited at 10 nm and TmPyPB is deposited at 50 nm.

8. The high-efficiency solution-processed blue-green organic light-emitting device according to claim 1, characterized in that, In the preparation of the cathode, lithium fluoride is deposited at 1 nm and aluminum is deposited at 100 nm.